A review on BCC-structured high-entropy alloys for hydrogen storage - Kong, Lingjie; Cheng, Bo; Wan, Di; Xue, Yunfei (Frontiers in Materials, 2023)
Recently, high entropy alloys (HEAs) with body-centred cubic (BCC) single phase structures have attracted wide attention in many fields including hydrogen storage, due to their unique structural characteristics and excellent performance. Its novel design concept provides more possibilities for the investigation of advanced hydrogen storage materials, in which several remarkable research works have been published, providing opportunities for the design of hydrogen storage materials with unprecedented properties. In this review, we combed through the definition and criteria of high entropy alloys, and summarized the current research status of body-centred cubic-structured high entropy alloys for hydrogen storage from multiple perspectives of composition designs, synthesis processes, and hydrogen storage properties. Moreover, the possible application scenarios and future research directions are analysed.